Liturgical hermeneutics of sacred scripture - Benini, Marco (Verbum Domini, 2023)
"The purpose of this book is to explore what a liturgical approach to the Bible looks like and what hermeneutical implications this might have: How does the liturgy celebrate, understand, and communicate Scripture? The starting point is Pope Benedict's affirmation that "a faith-filled understanding of sacred Scripture must always refer back to the liturgy""--